Efektivitas Model PBL Berbantuan Metode Enam Topi Berpikir untuk Meningkatkan Pemahaman Siswa Pada Pembelajaran Fisika - Raden Sumratul Handayani; Zakirman Zakirman (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to improve student learning outcomes on substance density material through the Problem Based Learning (PBL) model with the Six Hats of Thinking method. This type of research uses Classroom Action Research (PTK), the research sample is 7G grade students with a total of 32 students of UPT SMP Negeri 1 Gresik for the 2023-2024 academic year. The study was conducted two cycles. Method of data collection through tests. Based on the data obtained, it aims to determine student responses to improved learning outcomes. The data collected at PTK is in the form of quantitative data. The data is in the form of student learning outcomes. To analyze the level of achievement of student learning outcomes after the learning process per cycle by providing an assessment in the form of test questions per end of the cycle. This study brought the results that during the learning process there was an increase in student learning outcomes in cycle 1 reaching a grade average of 80 and cycle 2 showing an average increase of 92. Conclusion when applied PBL model with Six Hats Thinking method student learning outcomes increase.